EKONOMI SYARIâAH SEBAGAI LANDASAN DALAM AL-BAIâ (JUAL BELI) - Seff, Syaugi Mubarak (IAIN Antasari, 2012)
Normatively, Sharia economy as a part of Sharia law focuses on Islamic norms in economydeduced from al-Qurâan and al-Hadith as well as from other secondary sources. As a derivation ofIslam, Sharia economy will follow Islam in all aspects. Islam is a way of life as it provides acomplete guidance in the forms of legal norms for human beings, including in economic field.The norms of Sharia economy are: (a) partnership (b) the existence of moral drives (c) the exist-ence of social role.